Questions for In-Depth Reflection and Improvement of Music Teaching (Appendix to Chapters 10−19) - Kovačič, Bojan (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter presents a series of questions based on the ten chapters of the monograph (Chapters 10−19): Learning through Music Workshops, The Role of School Choirs, Music as a Means of Improving Concentration, Music and Motor Development, Learning with and without Musical Notation, Learning Music through Singing, Modern Music Technology at School, Multiculturalism in Music Education, Music Projects in Primary School, and Musical Genres. The questions are divided into four areas (lesson planning, lesson delivery, observation and evaluation, improvement and development) and enable teachers and students to reflect more closely on their own teaching practise.